Religiosity, Spirituality, and Nonsuicidal Self-Injury Among Adolescents: A Meta-Analysis of Cross-Sectional and Longitudinal Studies - Maya Aulya Saputri; Andrian Fajar Kusumadewi; Soewadi (HM Publisher, 2026)
Nonsuicidal self-injury (NSSI) represents a growing public health concern among adolescents worldwide, with prevalence rates reaching 44.8% in Asian populations. Spirituality and religiosity have been proposed as protective factors against self-injurious behaviours; however, the quantitative evidence for this association has not been systematically synthesised with rigorous methodological standards. This meta-analysis aimed to evaluate the association between spirituality/religiosity and self-injurious behaviours in adolescents and young adults, and to clarify distinctions between NSSI and suicidal behaviour. A systematic search of multiple databases (PubMed, PsycINFO, CINAHL, Web of Science) was conducted using predefined search terms related to spirituality, religiosity, religion, self-injury, self-harm, NSSI, and adolescent populations. Original research articles reporting quantitative data on the association between spirituality/religiosity and self-injurious behaviours were included. Ten studies met inclusion criteria for qualitative synthesis, of which six provided sufficient quantitative data for meta-analysis. Effect sizes were converted to standardised mean differences (Hedges' g) and pooled using a random-effects model (DerSimonian-Laird). Risk of bias was assessed using an adapted Newcastle-Ottawa Scale. Prediction intervals (PI) were calculated alongside 95% confidence intervals (CI). The pooled standardised mean difference was −0.67 (95% CI: −1.12 to −0.21; 95% PI: −2.18 to 0.85; p = 0.004), indicating a protective effect of spirituality/religiosity against self-harm. Substantial heterogeneity was observed (I² = 96%; τ² = 0.30), reflecting variability in study designs, populations, outcome measures, and religiosity constructs. Sensitivity analyses confirmed directional consistency of findings, though studies differ considerably in effect magnitude. Subgroup analyses identified potential differences by study design (cross-sectional vs. longitudinal) and geographic region, though these require cautious interpretation given limited sample numbers (k = 6). Meta-regression was limited by small sample size and collinearity between study characteristics. In conclusion, spirituality and religiosity demonstrated a protective association with reduced self-injurious behaviours among adolescents and young adults. However, the substantial heterogeneity, predominantly observational evidence base, concentration in Western populations, and inability to distinguish NSSI from suicidal behaviour in all studies necessitate cautious interpretation. These findings support further investigation of spiritual assessment in adolescent mental health, though clinical implications must be tempered by methodological limitations. Well-designed prospective studies examining cultural context, mechanisms of action, and distinctions between NSSI phenotypes are required.